Phase I-II study using DeltaRex-G, a tumor-targeted retrovector encoding a cyclin G1 inhibitor for metastatic carcinoma of breast - Bruckner, Howard W.; Chawla, Sant P.; Omelchenko, Nadezhda; Brigham, Don A.; Gordon, Erlinda M. (Frontiers in Molecular Medicine, 2023)
Background: Metastatic breast cancer is associated with a poor prognosis and therefore, innovative therapies are urgently needed. Patients and Methods: Endpoints: Dose limiting toxicity; Antitumor activity. Eligibility: > 18 years of age, pathologic diagnosis of breast carcinoma, adequate hematologic and organ function. Treatment: Dose escalation of DeltaRex-G 1-4 x 1011cfu intravenously thrice weekly x 4 weeks with 2-week rest period. Treatment cycles repeated if there is < Grade 1 toxicity until disease progression or unacceptable toxicity. Safety: NCI CTCAE v3 for adverse events reporting, vector related testing. Efficacy: RECIST v1.0, International PET criteria and Choi criteria for response, progression free and overall survival. Results: Twenty patients received escalating doses of DeltaRex-G from 1 x 1011 cfu to 4 x 1011 cfu thrice weekly for 4 weeks with a two-week rest period. Safety: > Grade 3 treatment-related adverse event: pruritic rash (n=1), no dose limiting toxicity, no replication-competent retrovirus, nor vector-neutralizing antibodies detected. No vector DNA integration was observed in peripheral blood lymphocytes evaluated. Efficacy: by RECISTv1.0:13 stable disease, 4 progressive disease; tumor control rate 76%; by PET and Choi Criteria: 3 partial responses, 11 stable disease, 3 progressive disease; tumor control rate 82%. Combined median progression free survival by RECIST v1.0, 3.0 months; combined median overall survival, 20 months; 1-year overall survival rate 83% for Dose Level IV. Biopsy of residual tumor in a participant showed abundant CD8+ killer T cells and CD45+ macrophages suggesting an innate immune response. Two patients with pure bone metastases had >12-month progression free survival and overall survival and are alive 12 years from the start of DeltaRex-G therapy. These patients further received DeltaRex-G + DeltaVax for 6 months. Conclusions: Taken together, these data indicate that (1) DeltaRex-G has a distinctively high level of safety and exhibits anti-cancer activity, (2) PET/Choi provide a higher level of sensitivity in detecting early signs of tumor response to DeltaRex-G, (3) DeltaRex-G induced 12- year survival in 2 patients with pure bone metastases who subsequently received DeltaVax immunotherapy, and (4) DeltaRex-G may prove to be a biochemical and/or immune modulator when combined with other cancer therapy/immunotherapy.